Lithuanian physicians practising abroad: Reasons to leave and conditions to return to Lithuania. A survey. (February 2023) - Radike, Monika; Zuromskis, Tadas
Highlights: Among Lithuanian doctors practicing abroad, emigration and return reasons are multifactorial. Top factors are economic reasons, perceived corruption and work environment. 37.2% of Lithuanian doctors practicing abroad to not plan to return. There are significant gender and training level-related discrepancies amongst emigration factors. Policy decisions should be multifactorial: salary increase alone may be insufficient. Abstract: This study aimed to assess the factors of emigration and return among Lithuanian doctors practicing abroad. A call for participation in an online survey was distributed via social media. Questions covered demographics, reasons to emigrate and factors that would favor returning to practice in Lithuania. Survey data were analysed with appropriate statistical methods. Out of 465 respondents, the majority (453/465, 97.4%) work in Europe. The majority (334/465, 71.8%) were women, and 304/465 (65.4%) were trainees (residents). The top three factors to emigrate from and come back to Lithuania were: economic reasons, perceived corruption and the work environment. Most respondents listed more than two factors to emigrate and return (>70% in each category). Out of all respondents, 230 (49.5%) reported an attractive net monthly salary for a full-time post in Lithuania to be >3500 EUR; 173/465 (37.2%) respondents declared intention of not returning to practice in Lithuania. There were statistically significant gender- and training level-related differences in emigration factors. In conclusion, doctors' reasons for leaving and returning to practice in Lithuania are multifactorial, with economic and non-economic circumstances prompting them to choose to work in another country.